In Vocational Education, Educator of The Errors Examine from The on A Real Program - Gul, H. (Elsevier Science Bv, 2015)
The aim of this study is identification on exam question by educator. In Vocational and training high school, second year exam question are selected as a sample. In this study, the second-class machine program students were asked by teachers final question were examined in the last five years. The review, basic courses, vocational courses and mathematics courses for: openness, open-ended questions, pointless, irrelevant and error on the side of a commission in the direction of the questions were examined. (C) 2015 The Authors. Published by Elsevier Ltd.
4th World Conference on Educational Technology Researches (WCETR) -- NOV 28-29, 2014 -- Univ Barcelona, Barcelona, SPAIN
Keywords: vocational training; defect question